Manipulative Shallow Processing Induced by Presuppositions and Topics: Theoretical Perspectives and Experimental Evidence - Lombardi Vallauri, Edoardo (Frontiers in Communication, 2021)
The paper shows that implicit strategies for questionable contents are frequent in persuasive texts, as compared to texts with other purposes. It proposes that the persuasive and manipulative effectiveness of introducing questionable contents implicitly can be explained through established cognitive patterns, namely that what is felt by addressees as information coming (also) from them and not (only) from the source of the message is less likely to be challenged. These assumptions are verified by showing examples of “implicitness of evidential responsibility” (essentially, presuppositions, and topics) as triggers of lesser attention in advertising and propaganda. A possible evolutionary path is sketched for three different pragmatic functions of presuppositions, leading to their availability for manipulation. The distraction effect of presuppositions and topics is also explained in relation with recent developments of Relevance Theory. Behavioral evidence that presuppositions and topics induce low epistemic vigilance and shallow processing is compared to recent neurophysiological evidence which does not confirm this assumption, showing greater processing costs for presuppositions and topics as compared to assertions and foci. A proposal is put forward to reconcile these apparently contrasting data and to explain why they may not be in contrast after all. Also due to natural language quick processing constraints (a “Now-or-Never processing Bottleneck”), effort devoted to accommodation of presupposed or topicalized new contents may drain resources from concurrent epistemic vigilance and critical evaluation, resulting in shallower processing.